1991
DOI: 10.1111/j.1540-8159.1991.tb04069.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Catheter Ablation for Wolff‐Parkinson‐White Syndrome Associated with a Coronary Sinus Diverticulum

Abstract: The case of a patient with Wolff-Parkinson-White syndrome undergoing attempted radiofrequency catheter ablation of a left posterior paraseptal accessory pathway is described. Coronary sinus venography revealed the presence of a large diverticulum attaching near the os. The electrogram recorded from a catheter placed in the narrow neck of the diverticulum revealed a very short atrioventricular time during sinus rhythm. The pathway was easily ablated using radiofrequency energy applied in the neck of the diverti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“…10 Furthermore, diverticulum in the proximal portion of the coronary sinus was also demonstrated to be related to the accessory pathway in the posteroseptal space. 11,12 …”
Section: Lin Et Al Pulmonary Vein Morphology In Patients With Afmentioning
confidence: 99%
“…10 Furthermore, diverticulum in the proximal portion of the coronary sinus was also demonstrated to be related to the accessory pathway in the posteroseptal space. 11,12 …”
Section: Lin Et Al Pulmonary Vein Morphology In Patients With Afmentioning
confidence: 99%
“…A posteroseptal AP is defined as one located posterior or apical to the orifice of the coronary sinus. [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] However, Dean et al 51 reported that the clinical designations of the septal regions are not entirely accurate; the socalled midseptum is the only true area of muscular septal area between the offset attachments of the mitral and tricuspid valves, while the socalled anterior and posterior septal areas, in reality, are the paraseptal areas anterior and posterior to the true septum. Furthermore, a higher incidence of catheter induced mechanical trauma of these septal pathways suggests a subendocardial location of these septal pathways.…”
mentioning
confidence: 99%
“…There have been several reports [2][3][4][5][6][7]16) about cases of Wolff-Parkinson-White syndrome with posteroseptal APs associated with CS diverticula. Those anomalies included an angulation, hypoplasia, localized narrowing, fistula and diverticula, but did not include dilatation (windsock appearance) of the CS.…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous reports [1][2][3][4][5][6][7][8][9] about coronary sinus (CS) anomalies related to posteroseptal accessory pathways (APs). Chiang CE et al 1) reported that some patients with APs in the left-free wall and posteroseptal area have CS abnormalities, such as an angulation, hypoplasia or diverticulum.…”
Section: Introductionmentioning
confidence: 99%